Methods for Flipping of Mammogram Images and Noise Removals - Bandyopadhyay, Prof. Samir Kumar (Innovative Journal of Medical and Health Sciences, 2019)
Cancer can be brain cancer, breast cancer, cervical cancer, etc. depending on the occurrence on the different parts of the body. to name a few. Cancer detected in later stage and it results into high mortality within few months. Early detection is the only hope for better prognosis and treatment. This paper proposed methods that digital mammogram image pair is initially pre-processed, the right oriented mammogram is flipped and any unwanted artifacts are removed from the image. Next noise removal is made using the Gaussian kernel. Key words: Digital mammography–Computer Aided Diagnosis–Breast Region–Seed